2020
DOI: 10.5539/gjhs.v12n11p177
|View full text |Cite
|
Sign up to set email alerts
|

Pakistan’s Community-based Lady Health Workers (LHWs): Change Agents for Child Health?

Abstract: BACKGROUND: In Pakistan’s high child mortality context, a large-scale Lady Health Worker (LHW) Program raises the need to look at whether LHWs are delivering their key mandate as agents of change for child health. This study examines the quantity and quality of LHW interactions with mothers for child health and their impact on mothers' knowledge and child health practices. METHODS: 1,968 mothers of children <2 years (n=1,968) were interviewed through a cross-sectional surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Although, quality of services provided by LHW are questioned in earlier studies in Sindh [29], the interventions designed for this project had a specific component of training, monitoring and supportive supervision of LHWs [30]. This was to ensure implementation of intervention as intended, with identification of issues and timely feedback provided to the Lady health supervisors (LHS) for subsequent improvement in service quality [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although, quality of services provided by LHW are questioned in earlier studies in Sindh [29], the interventions designed for this project had a specific component of training, monitoring and supportive supervision of LHWs [30]. This was to ensure implementation of intervention as intended, with identification of issues and timely feedback provided to the Lady health supervisors (LHS) for subsequent improvement in service quality [31], [32].…”
Section: Discussionmentioning
confidence: 99%
“…Another study from Sindh Pakistan depicted that LHWs are capable enough to identify SAM children without medical complications, while only 4% of the screened cases received appropriate counseling on medical and nutritional matters [17]. While examining the role of LHWs, particularly on immunization, nutrition, and early childhood illness, a study in two rural districts of Pakistan found that breastfeeding counseling by LHWs was received by 20% of mothers, and the majority of mothers did not know the correct use of ORS and early signs of pneumonia and other childhood diseases [18].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least one FGD was conducted with lady health workers (LHWs) of the respective union council since they are advocates for breastfeeding in the community and are aware of the societal dynamics. LHWs are frontline community health workers responsible for visiting the community and counseling mothers to exclusively breastfeed up to six months and to continue breastfeeding with complementary foods until two years [20]. There were 8 -12 participants in each FGD.…”
Section: Study Design and Data Collectionmentioning
confidence: 99%